Effect of antituberculous drugs on serum uric acid and urine uric acid excretion - Worawit Louthrenoo (2018)
© 2015 Wolters Kluwer Health, Inc. All rights reserved. Objectives: The aim of this study was to determine the effect of antituberculous drugs on serum uric acid (SUA), urine uric acid (UUA) excretion, and renal function. Methods: Patients with tuberculosis requiring a 6-month treatment course of antituberculous drugs (isoniazid, rifampicin, pyrazinamide, and ethambutol for 2 months, followed by isoniazid and rifampicin for a further 4 months) were included in this study. Serum uric acid, 24-hour UUA excretion, uric acid clearance (UACl), serum creatinine, and creatinine clearancewere determined at baseline and at the end of the secondweek, second month, and fourth month. Results: Sixteen of 50 patients completed the study. Their mean ± SD baseline SUA and UACl was 4.44 ± 1.72 mg/dL and 8.77 ± 7.03 mL/min per 1.73 m2, respectively. At the second week, a significant increase in SUA (9.78 ± 3.21 mg/dL, P < 0.001) and significant decrease in UACl (3.50 ± 2.50 mL/min per 1.73 m2, P = 0.001) were noted. These changes persisted through the second month, but returned to baseline value at the fourth month. Thirteen patients (81.25%) had hyperuricemia. The 24-hour UUA followed the same pattern as that of UACl but showed no statistical significance. There were no changes in serum creatinine or creatinine clearance. One patient had arthralgia, and another developed tuberculous arthritis. Conclusions: The hyperuricemic effect of pyrazinamide and ethambutol was due primarily to a decrease in UACl, which was reversible, and had no negative effect on the renal function. Arthralgia was uncommon and required no specific treatment.